PENGARUH SOCIAL MEDIA MARKETING, LITERASI KEUANGAN DAN SELF CONTROL TERHADAP PERILAKU KONSUMTIF DAN GAYA HIDUP HEDONIS ONLINE SHOPPING PRODUK FASHION PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS RIAU - Syahferi Rendi; Noviasari Henni; Wasnury Rendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The development of technological and communication advances resulted in faster socialchange, humans raced to show the things they achieved and the lifestyles they adopted.One of them is the hedonistic lifestyle. The Hedonistic lifestyle is a lifestyle that isoriented only towards pleasure and enjoyment. A hedonistic lifestyle can lead toconsumptive behavior. Consumptive behavior is a consumption activity that is not basedon needs but on desire and satisfaction. Consumptive behavior makes changes toconsumption patterns make a person irrational or simply because of emotional factors.This research aims to find out the influence of Social Media Marketing, FinancialLiteracy and Self Control on Consumptive Behavior and Hedonistic Lifestyle on Studentsof the Faculty of Business Economics, University of Riau. The number of samples in thisstudy as many as 114 students of the Faculty of Business Economics, Riau University asrespondents with non-probability sampling techniques. The method used is ExplanatoryResearch. Based on the results of the study found that social media marketing variableshave a significant effect on consumptive behavior. And the Hedonism And the Variablesof Financial Literacy and Self Control negatively affect Consumptive Behavior andHedonism.Keywords: Social Media Marketing, Financial Literacy, Self Control, Consumptive Behavior, Hedonistic Lifestyle